Geochemical and geological characteristics of the granitic batholith and Yuku concealed Mo–W deposit at the southern margin of the North China Craton. (9th December 2018) - Guo, Bo; Yan, Changhai; Zhang, Shouting; Han, Jiangwei; Yun, Hui; Tan, Heyong; Song, Qinchang; Meng, Fanxue
Abstract : Integrated gravity and magnetic prospecting in the Luanchuan ore cluster by the Henan Institute of Geological Survey has led to the recent discovery of the Yuku concealed porphyry Mo–W deposit. This research focuses on the geological, geochemical, and chronological features of the Yuku deposit, and it discusses the genesis of the deposit and its associated concealed granitic batholith. Skarn and/or hornfels occur in the contact zone between the granitic batholith and the wall rocks. The Mo mineralization is mostly hosted in porphyritic granites, whereas the large Mo–W deposits of the area (e.g., the Nannihu–Sandaozhuang Mo–W deposit) are mostly hosted in the skarn and hornfels. The laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) zircon U–Pb dating constrained three episodes of magmatic emplacement: (a) the porphyritic biotite monzogranite at 153.1 ± 1.2 Ma, (b) the ore‐causative porphyritic syenogranite at 147.1 ± 1.3 to 148.0 ± 1.6 Ma, and (c) the last porphyritic monzogranite at 130.0 ± 1.3 Ma. The granitic batholiths have high contents of SiO2, Al2 O3, and K2 O + Na2 O, obvious fractionation between the light and heavy rare earth elements [(La/Yb)N = 17.3–37.3], a negative Eu anomaly (δEu = 0.62–0.84), enrichment in Rb, Th, U, and Sr, and depletion of P and Ti. These features indicate the fractionation of plagioclase, amphibole, garnet, and rutile from the primary magmas or as residues in the source. The ε Hf ( t ) isotopic values of the zircons are concentrated between −21 and −13, with corresponding two‐stage model ages ( t DM2 ) between 2.1 and 1.7 Ga. The above characteristics indicate that the granitic batholiths were derived from the partial melting of the thickened lower crust during the Mesozoic to Cenozoic. The ore‐forming fluids emplaced in the contact zone between the batholith and the wall rocks resulted in the metasomatic alteration and the deposition of Mo–W mineralization.